PENGARUH INFORMASI KEUANGAN PERUSAHAAN DAN PROFILNYA TERHADAP UNDERPRICING - yuli soesetio (Accounthink, 2021)
This study aims to analyze the consistency of the effects of profitability, leverage, and liquidity information as well as the combination of non-financial information, namely the industrial sector type and the type of company ownership to underpricing by using secondary data obtained from prospectus of companies conducting IPOs for the 27 years. By using hierarchical regression analysis the liquidity ratio results consistently have a positive and significant effect on underpricing, while other financial variables consistently have no significant effect on underpricing. While the type of industrial sector and type of company ownership affect the consistency of the current ratio to underpricing